Using Cell-Based Strategies to Break the Link between Bronchopulmonary Dysplasia and the Development of Chronic Lung Disease in Later Life - Megan O'Reilly; Bernard Thébaud (Pulmonary Medicine)
Bronchopulmonary dysplasia (BPD) is the chronic lung disease of prematurity that affects very preterm infants. Although advances in perinatal care have changed the course of lung injury and enabled the survival of infants born as early as 23-24 weeks of gestation, BPD still remains a common complication of extreme prematurity, and there is no specific treatment for it. Furthermore, children, adolescents, and adults who were born very preterm and developed BPD have an increased risk of persistent lung dysfunction, including early-onset emphysema. Therefore, it is possible that early-life pulmonary insults, such as extreme prematurity and BPD, may increase the risk of COPD later in life, especially if exposed to secondary challenges such as respiratory infections and/or smoking. Recent advances in our understanding of stem/progenitor cells and their potential to repair damaged organs offer the possibility of cell-based treatments for neonatal and adult lung injuries. This paper summarizes the long-term pulmonary outcomes of preterm birth and BPD and discusses the recent advances of cell-based therapies for lung diseases, with a particular focus on BPD and COPD.